ANALISIS TINGKAT KEUSANGAN LITERATUR JURNAL NUSANTARA JOURNAL INFORMATION AND LIBRARY STUDIES TERBITAN TAHUN 2019 - Nur Rahmadhani Safitri; Tansah Rahmatullah; Undang Sudarsana (Nusantara Journal of Information and Library Studies (N-JILS), 2022)
This study aims to determine the level of obsolescence of literature cited in the 2019 Nusantara Journal Information and Library Studies (N-JILS) journal article or Volume 2 No. 1 and No. 2. The method used is a quantitative method with a Bibliometric approach. The source of data in this study is the bibliography of the journal N-JILS, published in 2019 Volume 2 No. 1 and No. 2. The variable examined in this study is the obsolescence of the literature while the indicator is the cited document. Data was taken from all articles published in 2019, namely 18 articles and examining the year of publication from the bibliography used in the article as many as 212 citations. that the level of obsolescence of document literature cited in all Nusantara Journal Information and Library Studies (N-JILS) articles published in 2019 or Volume 2 No. 1 and No. 2 is 8 years, so citations can be said to be obsolete, namely citations that have a year under 2011. In this case, there are citations under 2011, namely 105 citations with a percentage of 49.5% considered below the document obsolescence age point, while the same or above citations in 2011 were 107 citations with a percentage of 50.5% considered current/up-to-date.Keywords: Literature Obsolescence, Bibliometrics, Nusantara Journal Information and Library Studies (N-JILS)ABSTRAKPenelitian ini bertujuan untuk mengetahui tingkat keusangan literatur yang disitir pada artikel jurnal Nusantara Journal Information and Library Studies (N-JILS) tahun 2019 atau Volume 2 No. 1 dan No. 2. Metode yang digunakan adalah metode kuantitatif dengan pendekatan Bibliometrika. Sumber data dalam penelitian ini adalah daftar pustaka dari jurnal N-JILS terbitan tahun 2019 Volume 2 No. 1 dan No. 2. Variabel yang diteliti dalam penelitian ini adalah keusangan literatur sedangkan indikatornya adalah dokumen yang disitir. Data diambil dari semua artikel yang terbit pada tahun 2019 yaitu sebanyak 18 artikel dan meneliti tahun terbit dari daftar pustaka yang digunakan dalam artikel tersebut sebanyak 212 sitiran. bahwa tingkat keusangan literatur dokumen yang disitir pada seluruh artikel Nusantara Journal Information and Library Studies (N-JILS) terbitan tahun 2019 atau Volume 2 No. 1 dan No. 2 adalah 8 tahun jadi sitiran dapat dikatakan sudah usang adalah sitiran yang memiliki tahun di bawah tahun 2011. Dalam hal ini, terdapat sitiran yang di bawah tahun 2011 yaitu sebanyak 105 sitiran dengan persentase 49,5% dianggap berada di bawah titik usia keusangan dokumen, sedangkan sitiran yang sama atau di atas tahun 2011 adalah sebanyak 107 sitiran dengan persentase 50,5% dinilai terkini/mutakhir.